Poznavanje in pojavnost stresne urinske inkontinence med študentkami in študenti Fakultete za vede o zdravju - Slak, Vita (Šport (Ljubljana), 2023)
Urinary incontinence is defined as any involuntary leakage of urine, which can also be caused by certain forms of physical activity. A cross- sectional survey using a questionnaire was carried out among 162 students from the University of Primorska, Faculty of Health Sciences between October and December 2022. The findings indicate that approximately one third of the students experience at least occasional urine leakage, typically during coughing, sneezing, or physical activity. According to the short form of the questionnaire for determining urinary incontinence, 37.7 % of the participants have urinary incontinence, with the majority having a mild to moderate form (96.3 %). Although 74.1% of the respondents are regularly physically active, only 45.7 % perform pelvic floor muscle training at least occasionally. We did not identify any statistically sig- nificant association between the ground impact of each sport, physical activity or pelvic floor muscles training and urinary incontinence. Most of the participants acquired knowledge about urinary incontinence during their high school or college studies (38.9 %), while nearly 30 % obtained information from the internet. Therefore, it is crucial to improve knowledge transfer about urinary incontinence during educational programs and develop effective strategies to encourage individuals to incorporate pelvic floor muscle training into their daily routine.
Keywords: mišice medeničnega dna; raziskave; šport; telesna aktivnost; urinska inkontinenca; vadba